BODY IMAGE PASIEN DIABETES MILLITUS YANG MENGALAMI GANGGREN - Dania Dwi Nurcahyani; Cholik Harun Rosjidi; Lina Ema Purwanti (Health Sciences Journal, 2018)
AbstactDiabetes mellitus causes a DM complication where the wound complication are hard to recover, red to black, spoiled smell so there is amputation must be done in the end. This condition clearly disturbs body image which causes the patient feel embarrassed, low, and rejects this body condition. This purpose of this research is to know body image of gangrene diabetes mellitus patient in Dr. Sayidiman Magetan hospital.This research design is descriptive. The sampling technique is purposive sampling, with 589 populations. The sample is 49 respondents. The data collecting technique is questionnaire with T Score as data analysis technique.The result of this research is 25 respondents (51%) have positive body image, and 24 respondents (49%) has negative body image. This depends on gender, age, time of DM and gangrene suffer, living together, kind of dysfunction, education.Based on this research, it is hoped the patients can increase good body image in order to help the healing process, for next researcher suggested not to stop doing research about body image of gangrene diabetes mellitus with wider populations so reach optimal carefulness.Keyword : Body Image, Patient, Diabetes Mellitus, Gangrene. AbstrakPenyakit DM mengakibatkan salah satu komplikasi DM dimana komplikasi pada luka sukar sembuh, luka berwarna merah kehitaman, berbau busuk yang akhirnya dilakukan amputasi kondisi ini jelas mengganggu body image yang mengakibatkan pasien merasa malu, rendah diri, dan tidak menerima keadaan tubuhnya. Penelitian ini diuntukkan mengetahui body image pasien DM yang mengalami ganggren di RSUD dr.Sayidiman Magetan. Desain penelitian yang digunakan adalah deskriptif. Teknik sampling yang digunakan adalah Purposive Sampling, dengan populasi 589 orang, sampel berjumlah 49 responden, teknik pengumpulan data dengan kuisioner, teknik analisa menggunakan skor T. Hasil penelitian dari 49 responden didapatkan hasil 25 responden (51%) memiliki body image positif, dan 24 responden (49%) memiliki body image negatif. Hal ini dipengaruhi jenis kelamin, usia, lama menderita DM, lama menderita ganggren, tinggal bersama, jenis gangguan fungsi, pendidikan. Berdasarkan hasil penelitian diharapkan pasien dapat meningkatkan body image yang baik agar membantu proses penyembuhan dengan cepat, bagi peneliti selanjutnya disarankan untuk tidak berhenti melakukan penelitian tentang body image pasien DM yang mengalami ganggren dengan populasi yang lebih banyak agar tercapai ketelitian penelitian optimal.Kata Kunci : Body Image, Pasien, Diabetes Mellitus, Gangren